EXPERIMENTAL ANALYSIS OF THE EFFECT ADDITION HEAT COVER IN DISTILLATION REACTOR - Gusti Ngurah Ardana; Made Anom Adiaksa; Putu Darmawa (Logic : Jurnal Rancang Bangun dan Teknologi, 2022)
Distillation is the process of separating two or more components of a liquid based on their boiling points in which the material to be evaporated is contained. Distillation is simply done by heating/evaporating the liquid and then changing the vapor phase to liquid with the help of a condenser. Research on the distillation column or reactor has been carried out to improve the distillation system but is still discussing the reactions that occur due to heating and the final product of the distillation process. An analysis based on the second law of thermodynamics is developed, known as exergy analysis to obtain information about the thermodynamic efficiency and locations that have low energy efficiency so that energy savings can be targeted. The distillation reactor as one of the vital tools at the separation stage is very important to note is the manufacture of the reactor. To reduce heat loss that occurs by adding a heat protective layer (heat cover) on the distillation reactor. The heat protection materials used are burlap sacks and glass wool to be implemented for rural communities and also become prototypes of appropriate technology application tools. The use of a 3 cm jute alloy on the inside and 3 cm glass wool on the outside gave the highest heat transfer value of 7864.21 watts. The increase was 43% of those who only used burlap. An increase of 37% over those using only glass wool. A 3% improvement over an alloy of 3 cm glass wool inside and 3 cm burlap on the outside.